1898-99 Ala. Laws 1046, ch. 549 - (:unkn) unknown (General Publisher, 1899)
Granted the town the authority to regulate, tax, and license dealers in Pistols, pistol cartridges, Bowie knives, and dirk knives. Licenses shall not exceed fifty dollars.
--
Keywords: TAX - DEALERS